2021
DOI: 10.5530/ijpcs.2021.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Pharmacists about Nuclear Pharmacy Services in Saudi Arabia

Abstract: Goal: In this study, we aimed to explore the nuclear pharmacy perception in the Kingdom of Saudi Arabia. Methods: This is a 4-month cross-sectional study including all pharmacists and pharmacy interns in the Kingdom of Saudi Arabia. Students were excluded from this study. We distributed the electronic survey to the participants which consisted of two parts. The first part collected demographic information, and the second part collected information of perception of pharmacists about nuclear pharmacy services an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…[5][6][7][8] Additional research examined specific knowledge or perceptions regarding pharmaceutical care. [9][10][11][12][13] Numerous guidelines discussed the cross-sectional model in research practice and the model's advantages and disadvantages. [13][14][15][16][17][18][19][20][21][22] However, the policies and procedures for cross-sectional research are not well documented or are only found infrequently in the literature search database.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Additional research examined specific knowledge or perceptions regarding pharmaceutical care. [9][10][11][12][13] Numerous guidelines discussed the cross-sectional model in research practice and the model's advantages and disadvantages. [13][14][15][16][17][18][19][20][21][22] However, the policies and procedures for cross-sectional research are not well documented or are only found infrequently in the literature search database.…”
Section: Introductionmentioning
confidence: 99%